The glomalin-related soil protein content as influenced by crop rotation (spring barley monoculture/Norfolk crop rotation), straw application, and tillage - Balík, Jiří; Ryant, Pavel; Suran, Pavel; Dryšlová, Tamara; Smutný, Vladimír; Černý, Jindřich; Kulhánek, Martin; Sedlář, Ondřej; Mazánek, Petr (Frontiers in Soil Science, 2026)
Long-term field experiments were established in 1969 at the gleyic fluvisol to assess the effects of soil management on soil organic matter and glomalin-related soil proteins. Two systems were studied: Hordeum vulgare L. monoculture (spring barley monoculture, SBM) and Norfolk crop rotation (NCR) consisting of the following crops: Trifolium or Medicago spp. (clover/alfalfa), Triticum aestivum L. (winter wheat), Zea mays L. (maize), and Hordeum vulgare L. (spring barley). Experimental factors included: i) tillage-ploughing (PL, 22 cm) vs. chiselling (CC, 12–14 cm); ii) straw management-straw removed (SR) vs. straw incorporated (SI; only in SBM); iii) soil sampling depths-0–10 cm, 10–20 cm, and 20–30 cm. Treatments were arranged as split-strip plots with four replications. Chisel cultivation enhanced total glomalin content and increased carbon in soil organic matter (CSOM) content compared to ploughing, particularly in upper soil layers (0–20 cm) in the SBM. Straw incorporation promoted CSOM accumulation more effectively under ploughing than under chisel cultivation but had no measurable effect on the easily extractable glomalin-related soil protein content. The Norfolk crop rotation system significantly improved both CSOM levels and the glomalin-related soil protein content. These results highlight that adopting conservation-oriented soil management can improve soil structure and carbon retention, providing practical guidance for farming systems aiming to maintain long-term soil fertility